Fitness promotion in college: the relationships among students’ perceived physical literacy, knowledge, and physical fitness - Long, Bin; Liu, Yang; Chen, Senlin; Yang, Yiwu; Tang, Suna; Yang, Jimei; Wang, Yuhuai (Frontiers in Psychology, 2024)
Purpose The purpose of this study was to examine the relationships among perceived physical literacy (PPL), knowledge of physical activity and fitness (PAF knowledge), and physical fitness. Methods Undergraduates (N = 968, female = 414; Mage = 18.64) from a public university in central China completed a simplified Chinese version of the PPL instrument, an online test for PAF knowledge, and seven health-related physical fitness tests. The PPL includes three dimensions: (a) confidence and physical competence, (b) motivation, and (c) interaction with the environment. The fitness tests measured lung capacity, body mass index (BMI), and performances in 800 (female)/1000 (male) meters run, 50 meters dash (50 M), sit-up (female) / pull-up (male), standing long jump (SLJ), and sit-and-reach. Results PPL and its dimensions significantly predicted six fitness test performances both in male (β: −0.42 – 0.37; p < 0.01–0.05; R2: 0.01–0.13) and female (β: −0.59 – 0.49; p < 0.01–0.05; R2: 0.03–0.13) students. PAF knowledge (β: −0.17 – 0.18; p < 0.01–0.05; R2: 0.01–0.05) significantly predicted BMI (males) and performances in 50 M (females) and SLJ (females) tests. Conclusion To support college students’ fitness development and maintenance, tailored physical activity and fitness promotion programs are needed to strengthen students’ PPL and PAF knowledge.